2002
DOI: 10.1007/s11664-002-0234-0
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Cr doping of ZnSe by molecular beam epitaxy

Abstract: INTRODUCTIONThe incorporation of transition-metal ions into a semiconductor host is an effective technique for producing material useful for fabricating lasers. In particular, the small crystal-field splitting found for transition-metal ions in II-VI materials allows for laser operation in the 2-5-m spectral range. 1 Lasers based on these materials are of interest for commercial and military applications for optical identification of chemicals. Many molecules have strong and unique absorption spectra in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…A series of Cr-doped ZnSe and ZnTe epilayers for mid-IR optical studies were grown by molecular beam epitaxy (MBE) on semi-insulating GaAs (001) substrates [34][35][36][37]. Chromium concentrations in the doped epilayers ranged from 10 14 to 10 20 cm −3 .…”
Section: Tm Doped Ii-vi Thin-filmsmentioning
confidence: 99%
“…A series of Cr-doped ZnSe and ZnTe epilayers for mid-IR optical studies were grown by molecular beam epitaxy (MBE) on semi-insulating GaAs (001) substrates [34][35][36][37]. Chromium concentrations in the doped epilayers ranged from 10 14 to 10 20 cm −3 .…”
Section: Tm Doped Ii-vi Thin-filmsmentioning
confidence: 99%
“…To our knowledge, the only experimental data relating an increase of the lattice parameter value for MBE-grown (Zn,Cr)Se layer to an increase of Cr content are presented in Ref. [18]. According to the authors, the X-ray diffraction and the reflection high-energy electron diffraction (RHEED) indicated that high structural layer quality was maintained for Cr incorporation up to ∼10 19 atoms cm −3 (corresponding to the Zn 1−x Cr x Se mixed crystal composition x ∼ 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…The precision of XRD measurements is not as good as that for HRXRD so we will not use the numerical values given in Ref. [18] for our estimations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b the total Cr concentration in the studied film (without distinguishing the valence state of the chromium) is 3 times larger than the one of the single crystal. Contrarily to the Cr 2 + :ZnSe films deposited by MBE [22], the Cr concentration in both studied samples is quite uniform along the thickness.…”
Section: Composition Of the Samplesmentioning
confidence: 92%